Canadian Consumer Preferences Regarding Gene-Edited Food Products - Vasquez, Oswaldo; Hesseln, Hayley; Smyth, Stuart J. (Frontiers in Genome Editing, 2022)
Innovations in food production and processing have largely remained ‘behind the scenes’ for decades. The current nature of social media and calls for increased transparency regarding food results in a new landscape where consumer product demands are more important than ever, but are increasingly based on limited, or incorrect, information. One area where consumer awareness is rapidly emerging is the area of gene-edited food products. This article uses a consumer survey to gather perceptions regarding food safety, gene editing and willingness to consume for three gene-edited food products. Four factors were found to strongly influence consumer perceptions: trust in the Canadian food safety system; food technology neophobia scores; knowledge of genetics; and self-knowledge of gene editing. The survey of 497 Canadians found that 15% identified as neophobics and 12% as neophilics. The majority of participants identified as neutral. When presented with various food values, participants indicated that nutrition, price, and taste were the three most important values. A participants’ willingness to consume gene-edited food products strongly correlated with neophobic and neophilic preferences, with neophobics unwilling to consume and neophilics being uncertain. The only food value that strongly affects consumer willingness to consume is the environmental impact of a products’ production. Canadian consumers have a moderate to high level of trust in Canada’s food safety system, but this level of trust fails to carry over to food products produced through innovative technologies; however, consumers express a higher level of trust in gene-edited technology than genetically modified technology.